Panji in the Age of Motion; An investigation of the development of Panji-related arts around Java - Perkasa, Adrian (Wacana, Journal of the Humanities of Indonesia, 2020)
The first half of the twentieth century in Indonesia is often remembered as the Age of Motion. The term “motion” (pergerakan) is invariably used in history textbooks for students and in the official Indonesian historiography: Sejarah nasional Indonesia (Kartodirdjo, Poesponegoro, and Notosusanto 1975; Poesponegoro and Notosusanto 2008) and in the new edition, Indonesia dalam arus sejarah (Lapian and Abdullah 2012). Political movements in Indonesia always dominated the discourses of pergerakan at the expense of developments in other sectors, including culture. This cultural development, particularly in Java, was intricately intertwined with the upsurge in Javanese and then Indonesian nationalism, an expansion of modernity and Islamic revivalism. Topeng Panji with all of its forms around Java is symptomatic of this development. This paper is an initial investigation into the developments of topeng Panji across Java in the Age of Motion. By tracing the social and cultural histories from the perspective of the bureaucrats, artists, and government officials who wrote in books, journals, and other contemporary sources, this study aims to highlight topeng Panji and its development during that period.